2. DETEKSI LEUKOSIT URINE ORANGUTAN SUMATERA (Pongo abelii) MENGGUNAKAN STRIP TEST SEMIKUANTITATIF DI PUSAT REINTRODUKSI JANTHO (Detection of Leucocyte on Sumatran Orangutan (Pongo abelii) Urine Using Semiquantitative Strip Test in Jantho’s Reintroduction Center) - Meuthya Sr; Rusli Rusli; Erdiansyah Rahmi (Universitas Syiah Kuala, 2016)
The aim of this study was to find out the information about sumatran orangutan urine leucocyte as a medical record of them at Cagar Alam Pinus Jantho Reintroduction Center, Aceh Besar. Urine samples were collected from ten sumatran orangutans which come from forest, around cages, and in the cage. The urine was collected in the morning when orangutan woke up and left the nest or before first feeding for orangutans which were in the cages. The replication test was done six times within one month. Urine examination was carried out directly after urine collection by soaking the strip test in 5 ml urine for 120 second. The data was analyzed by qualitative descriptive method and the result was semiquantitative based on the discoloration scale: negative, trace (±15 leucocyte/μL), +1 (70 leucocyte/μL), +2 (125 leucocyte/μL), and +3 (500 leucocyte/μL). The result showed that the average of leucocyte from 4 orangutans which were in the cages (Ego, Wenda, Miky, and Ontong) was ±15 leucocyte/μL, while Ayu Ting Ting for the first test had the highest level of leucocyte (500 leucocyte/μL) then decreased on the next test. Coty, Ruben, Yusniar (arround the cages) had variative leucocyte values every week. Two orangutans in the forest (Kamelia and Brokoli) had negative value for urine leucoyte.Key words: leucocyte, sumatran orangutan, strip test, urine